Dari Kerajaan Menjadi Republik: Transformasi dan Konfrontasi Kepemimpinan Raja Idris Serta Kebijakan Muammar Khadafi Di Libya Abad 20 - Subkhana Adzim Baqi; Raka Zikrilah (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
The transition from monarchy to republic in Libya was one of the most significant political changes in the 20th century. The fall of King Idris and the rise of Muammar Gaddafi reflected the clash between traditional leadership and revolutionary charismatic leadership. This study aims to analyze the factors that caused the transition and its impact on Libya's political structure. This study uses a historical method with four stages, namely heuristics, source criticism, interpretation, and historiography. The results of the study indicate that the transition from monarchy to republic was triggered by dissatisfaction with the leadership of King Idris who was considered too dependent on the West and less responsive to nationalist aspirations. On the other hand, Gaddafi took advantage of anti-Western sentiment and Arab nationalism to seize power through a military coup. However, although the republican system under Gaddafi offered change, this system actually led to an authoritarian government that limited political freedom and caused long-term instability. This study emphasizes that changes in the political system without mature institutional readiness can lead to instability. This transition is not only a change of leader, but also a major transformation that has had an impact on the direction of Libyan politics to this day.